A Double-Blind, Placebo-Controlled Trial Demonstrating the Safety, Tolerability, and Pharmacokinetics of Single, Escalating Oral Doses of RTI-336 - Carroll, F. Ivy; Kosten, Thomas R.; Buda, Jeffrey J.; Wang, Laurene; Walters, Bradford B. (Frontiers in Pharmacology, 2018)
Background: Preclinical and clinical data suggest that a compound which binds potently to and inhibits the dopamine transporter, but with a slower onset and offset rate than cocaine and with less abuse potential and psychomotor stimulant activity, could be a useful adjunct in the treatment of cocaine dependence. Methods: We assessed the safety, tolerability, and pharmacokinetics of oral single doses (0.3, 1, 3, 6, 12, 20 mg) of such an analog, RTI-336, in a randomized, double blind, placebo controlled trial in healthy adult males. Pre-dose and post-dose safety assessments included physical examinations (including neurological examination); orthostatic vital signs; 6 lead continuous electrocardiogram (ECG) telemetry monitoring pre-dose to 8 hours post-dose; 12 lead ECGs; clinical chemistry, hematology, and urinalysis; Mini Mental Status Examinations; and adverse events (AE). RTI-336 pharmacokinetics (PK) were assessed in plasma and urine. Results: 22 participants were enrolled. RTI-336 was well tolerated up through the maximum evaluated dose of 20 mg. PK analyses demonstrated good absorption, with peak plasma concentrations (Cmax) occurring around 4 hours post-dose and consistent half-lives of around 17 hours for the 6, 12, and 20 mg doses. Plasma drug exposure and Cmax increased in proportion to dose. Only 0.02% of RTI-336 was excreted unchanged in urine. Active metabolites UC-M5, UC-M8, and UC-M2 were measurable in plasma and urine, with plasma Cmax of UC-M5 and UC-M8 exceeding that of RTI-336. Three AE possibly were related to RTI-336 and resolved with discontinuation; the one serious AE was unrelated to RTI-336. 2 participants had transient and mild serum total bilirubin elevations (<1.5x upper limit of normal) at day 3 post-dose which resolved by day 8 post-dose. Conclusions: All doses including the highest (20 mg) showed excellent safety and tolerability, and further studies in humans are warranted.